MAIN TRENDS AND PROBLEMS OF FORMING STANDARD OF HIGHER EDUCATION OF FUTURE FITNESS TRAINERS IN PEDAGOGICAL THEORY - Vasylenko, Maryna N. (Educological discourse, 2016)
The article presents modern trends of higher physical education reform in the context of global education policy (globalization, internationalization, Europeanization). The main risks and benefits of entering of national physical education into the EU are indicated in the article. It was found that training of future fitness trainers in higher education was the subject of a limited number of researches by domestic and foreign scientists. In most cases, authors confine themselves to one of a component of this training. The conclusion is that it is necessary to develop theoretical and methodological foundations for future fitness trainers’ training in higher education.